The Experiences of Registered Nurses Who are Injured by Interpersonal Violence While on Duty in an Emergency Department. Issue 4 (October 2016) - Wright-Brown, Salena; Sekula, Kathleen; Gillespie, Gordon; Zoucha, Rick
Abstract : ABSTRACT: A successful career as an emergency department registered nurse (RN) requires the ability to respond quickly to a wide variety of potentially life-threatening illnesses and injuries. The unpredictable nature of this work can evoke emotional and physical stress on the RN beyond that which might be experienced by nurses who work in more stable, controlled, and predictable environments. Emergency healthcare is predicated on unexpected illness or injury leading to unscheduled episodic work. Additional stress is placed on the RN by the potential for violence that occurs in emergency departments. This mixed method pilot study describes the experiences of RNs who have been injured by violence while working in an emergency department. The study included an assessment of the job satisfaction of RNs in the emergency department based on Porter's Need Satisfaction Scale. This scale addresses need fulfillment in five categories: security, social, esteem, autonomy, and self-actualization. The self-actualization subscale measures satisfaction with personal growth, worthwhile accomplishments, and self-fulfillment. During the second strand of the study, phenomenological informed interviews were held with RNs who had been injured while on duty in an emergency department. The findings indicate that the largest reported gaps between the current state and the desired state were found in the area of security and self-actualization. RNs in the emergency department who answered the survey indicated that they desired a safe, secure worksite where they could achieve personal growth, worthwhile accomplishments, and self-fulfillment; but they were not satisfied with their current status in these areas.